Expression Level of IL-6 Secreted by Bone Marrow Stromal Cells in Mice with Aplastic Anemia. (18th June 2013) - Chen, Yong Feng; Wu, Zhong Min; Xie, Cong; Bai, Shi; Zhao, Li Dong
Abstract : Parasecretion of the hematopoietic cytokines is considered as one of the mechanisms account for bone marrow hematopoiesis disorder. In this study, the level of IL-6 secreted by bone marrow stromal cells from a mouse model of aplastic anemia was analyzed. The aplastic anemia mouse model was established with cyclophosphamide in combination with chloramphenicol and 60 Co γ radiation. The impairment of bone marrow hematopoiesis induced by irradiation and chemotherapeutic drugs was subsequently characterized by peripheral blood cell count, pathomorphological changes, and apoptosis rate. Furthermore, the in vitro proliferation of bone marrow stromal cells (BMSC) and the IL-6 secretion levels of BMSC were analyzed. In our model of aplastic anemia, the number of peripheral blood cells and bone marrow cells (BMC) were notably decreased, and the apoptosis rate of BMC increased. Furthermore, the proliferation of BMSC was obviously impeded while the IL-6 secretion levels of BMSC significantly increased. The findings of our study suggested that the IL-6 secretion level may be enhanced to some extent by the induction of aplastic anemia caused by irradiation and chemotherapeutic drugs and that the abnormal level of IL-6 might probably interfere with the stability of the bone marrow hematopoietic microenvironment.